2008
DOI: 10.4161/auto.5524
|View full text |Cite
|
Sign up to set email alerts
|

Altered macroautophagy in the spinal cord of SOD1 mutant mice

Abstract: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
103
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(117 citation statements)
references
References 21 publications
14
103
0
Order By: Relevance
“…Indeed, we observed increased levels of LC3II across disease progression corresponding with previous literature (Morimoto et al 2007, Li et al 2008, Tian et al 2011). Similarly we found elevated ULK1 phosphorylation at PND 90, suggesting that AMPK may signal cytoprotective mechanisms such as the clearance of protein aggregates (Hetz et al 2009, Crippa et al 2010.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, we observed increased levels of LC3II across disease progression corresponding with previous literature (Morimoto et al 2007, Li et al 2008, Tian et al 2011). Similarly we found elevated ULK1 phosphorylation at PND 90, suggesting that AMPK may signal cytoprotective mechanisms such as the clearance of protein aggregates (Hetz et al 2009, Crippa et al 2010.…”
Section: Discussionsupporting
confidence: 90%
“…Dysfunction of the autophagylysosome system may contribute to neuronal degeneration in several neurodegenerative diseases [6,8,9] . Our previous study and those of others have shown the accumulation of autophagic vacuoles in the spinal cord of SOD1 G93A mice and ALS patients, suggesting a role of autophagy in the pathogenesis of ALS [5,10] . We further reported that targeting autophagy with rapamycin, a classic autophagy activator, significantly exacerbates motor neuron loss and fails to Neurosci Bull August 1, 2015, 31 (4): [459][460][461][462][463][464][465][466][467][468] 460 remove the abnormal mutant SOD1 aggregates, raising the possibility of autophagic flux defects in SOD1 G93A mice [11] .…”
Section: Introductionsupporting
confidence: 56%
“…In this study, mice overexpressing the G93A mutation of SOD1 were used to model ALS. The underlying pathogenic mechanisms, although still largely unknown, probably involve the aggregation of misfolded proteins [5,6] .…”
Section: Introductionmentioning
confidence: 99%
“…Dysregulation of autophagy has been reported to contribute to ALS pathology both in human patients and animal models [44,57]. Li et al [58] reported a progressive increase of the relative amount of LC3b II from 90 to 140 days of age in SOD1 G93A mice, accompanied by accumulation of autophagic vesicles. These findings could be the result of autophagic flux impairment.…”
Section: Discussionmentioning
confidence: 99%